ANALISIS PENGARUH ELECTRONIC WORD OF MOUTH TWITTER TERHADAP KEPUTUSAN PEMBELIAN - Fatmasari, Fitri; Novaria, Rachmawati; Tjahjono, Endro (Jurnal Dinamika Administrasi Bisnis, 2015)
Progress is rapidly increasing social media development in line with advances information technology. Sharing of experiences between the consumer of a product can be done through the online media that can be accessed by other potential customers and are able to influence the purchase decisions of these products. This study aims to analyze the influence of electronic word of mouth Twitter on purchasing decisions at Restoran Mie Akhirat, Surabaya. Social media is a very fast growing Twitter, Twitter large number of potential users in conducting marketing activities. Methods of analysis used in this study is multiple regressions analysis. The results showed that the electronic word of mouth Twitter has a strong influence on purchasing decisions at Restoran Mie Akhirat, Surabaya.Keywords: electronic word of mouth, social media marketing, purchase decisions